DULIP: A Dual Luminescence-Based Co-Immunoprecipitation Assay for Interactome Mapping in Mammalian Cells. Issue 21 (23rd October 2015) - Trepte, Philipp; Buntru, Alexander; Klockmeier, Konrad; Willmore, Lindsay; Arumughan, Anup; Secker, Christopher; Zenkner, Martina; Brusendorf, Lydia; Rau, Kirstin; Redel, Alexandra; Wanker, Erich E.
Abstract: Mapping of protein–protein interactions (PPIs) is critical for understanding protein function and complex biological processes. Here, we present DULIP, a dual luminescence-based co-immunoprecipitation assay, for systematic PPI mapping in mammalian cells. DULIP is a second-generation luminescence-based PPI screening method for the systematic and quantitative analysis of co-immunoprecipitations using two different luciferase tags. Benchmarking studies with positive and negative PPI reference sets revealed that DULIP allows the detection of interactions with high sensitivity and specificity. Furthermore, the analysis of a PPI reference set with known binding affinities demonstrated that both low- and high-affinity interactions can be detected with DULIP assays. Finally, using the well-characterized interaction between Syntaxin-1 and Munc18, we found that DULIP is capable of detecting the effects of point mutations on interaction strength. Taken together, our studies demonstrate that DULIP is a sensitive and reliable method of great utility for systematic interactome research. It can be applied for interaction screening and validation of PPIs in mammalian cells. Moreover, DULIP permits the specific analysis of mutation-dependent binding patterns. Graphical abstract: Highlights: DULIP is a dual luminescence-based co-immunoprecipitation assay suitable for systematic analysis of PPIs. DULIP generates quantitative interaction scores. DULIP reliably detects PPIs with high sensitivity and specificity. DULIP measures the effects of point mutations on interaction strength.